P2.035 As Nucleic Acid Amplification Testing For Neisseria Gonorrhoeae Increases is Culture Confirmation Decreasing?. (13th July 2013) - Perry, M E O; Haidari, G; White, J A
Abstract : Background: With the advent of nucleic acid amplification tests (NAATs) to detect Neisseria gonorrhoeae (GC) the use of selective culture is now reserved largely for symptomatic patients or confirmation of GC NAAT-positive results prior to treatment. The importance of culture remains greater than ever for monitoring antimicrobial susceptibility in the face of emerging GC resistance. Aim: We hypothesise that there is decreased likelihood of culture sampling at initial testing prior to treatment and thus there might be fewer culture samples available for antimicrobial susceptibility. Methods: A list of GC-positive cases in 2011 and 2012 was generated from the laboratory. All cases were reviewed and recorded as having had: culture not taken, culture taken & negative, culture taken & positive. Annual cases were compared for the proportion being cultured prior to treatment, culture positivity rate and changes over time were assessed. Results: Conclusion: In our busy urban Genito Urinary Medicine (GUM) clinic we have shown that despite the increased ease and sensitivity of GC NAATs, GC culture has been sustained. The increase in the number of GC cases seen in 2012 is commensurate with an increase in testing episodes, yet the proportion with cultures taken pre-treatment actually increased from 64% in 2011 to 78% in 2012. Nonetheless, culture positivity has remained stable at 50% between 2011 and 2012. This is likely a result of our large MSM cohort, with high rates of rectal & throat infections in which culture sensitivity is substantially lower. Reassuringly we had no confirmed cases of ceftriaxone-resistant GC; yet it remains imperative to culture all patients prior to treatment to identify emerging resistant strains.